Impact of clopidogrel loading dose on clinical outcome in patients undergoing percutaneous coronary intervention: a systematic review and meta-analysis. Issue 2 (23rd August 2010) - Siller-Matula, Jolanta M; Huber, Kurt; Christ, Günter; Schrör, Karsten; Kubica, Jacek; Herkner, Harald; Jilma, Bernd
Abstract : Context: Enhanced platelet inhibition by clopidogrel decreases the risk of ischemic events but carries a risk for a concomitant increase in bleeding. Objectives: To compare the efficacy and safety of two clopidogrel loading regimens (300mg vs. 600mg) in patients undergoing percutaneous coronary intervention (PCI) at one month after start of therapy. Data sources: A systematic literature search of MEDLINE, EMBASE, CENTRAL, and Web of Science databases using predefined search terms for relevant articles in any language. Study selection and data extraction: Randomised controlled trials and non-randomised studies reporting adjusted effect estimates were included. Summary estimates of the risks ratios (RRs) with therapy were calculated using a random-effect model. Outcomes evaluated were combined major adverse cardiovascular events (MACE) and major bleedings. Results: Seven studies met the inclusion criteria and included 25, 383 patients. A 600mg clopidogrel loading was associated with a 34% relative risk reduction of MACE (RR=0.66; 95% confidence intervals CI=0.52-0.84; p<0.001). Sub-analysis revealed a 47% risk reduction of MACE in randomised trials (RR=0.53; 95%CI=0.32-0.88; p=0.01) and a 31% relative risk reduction in non-randomised trials (RR=0.69; 95%CI=0.54-0.90; p=0.005) in patients receiving 600mg loading with clopidogrel. In patients suffering from acute coronary syndrome, 600mg clopidogrel loading was associated with a 24% relative risk reduction in MACE (RR=0.76; 95%CI=0.60-0.95; p=0.02). Importantly, the 600mg clopidogrel loading dose was not associated with an increased risk of major bleedings (RR=0.91; 95%CI=0.73-1.15; p=0.44). Conclusions: This meta-analysis demonstrates that intensified clopidogrel loading with 600mg reduces the rate of major cardiovascular events without increase in major bleeding compared to 300mg in patients undergoing PCI during one month follow-up.